Impact of preloading either dairy or soy milk on postprandial glycemia, insulinemia and gastric emptying in healthy adults - Sun L. (Dr. Dietrich Steinkopff Verlag GmbH and Co. KG, 2020)
10.1007/s00394-015-1059-y